Experimental Performance Evaluation of a Hyper-Branched Polymer Electrolyte for Rechargeable Li-Air Batteries - Das, Susanta K.; Sarkar, Abhijit; Berry, K. Joel (Frontiers in Energy Research, 2020)
A hyper-branched polymer (HBP) electrolyte is synthesized for rechargeable lithium-air (Li-air) battery cell and experimentally evaluated its performance in actual battery cell environment. Several real-world battery cells were fabricated with synthesized HBP electrolyte, pure lithium metal as anode and an oxygen permeable air cathode to evaluate reproducibility of the rechargeable Li-air battery cell. The effect of various conditions such as various HBP based electrolytes, discharge current - 0.1mA 0.5mA, cathode preparation processes and carbon contents on the battery cell performance were experimentally evaluated using the fabricated battery cells under dry air condition. Detailed HBP electrolyte synthesis procedures and experimental performance evaluation of Li-air battery cell for various conditions are presented. The experimental results showed that different conditions and processes significantly affect the Li-air battery performance. Upon taking into account the effect of different conditions and processes, optimized HBP electrolyte materials, cathode process and conditions were determined. Several Li-air battery cells were fabricated with optimized conditions and optimized battery cell materials to determine the reproducibility and performance consistency. Experimental results showed that over 55 65 hours of discharge occurred over 2.5V terminal cell voltage with all three optimized Li-air battery cells. It implied that the optimized Li-air battery cells were reproducible and were able to hold charge over 2.5V for more than two days. Experimental results of the Li-air battery cell with further refined optimized materials revealed that the battery cell can discharge more than 10 days (i.e. more than 250 hours) at or above 2.0V. The experimental results also showed that the Li-air battery discharge time got shorter as the discharge-charge cycle increases due to increase in internal resistances of battery cell materials. The experimental results confirmed that the lithium-air battery cell can be reproduced without loss of performance and can hold charge more than 10 days at or over 2.0V. The investigation results obtained may usher a pathway to manufacture a long-life rechargeable Li-air battery cell in the near future.